Association Between Marijuana Use and Cardiovascular Diseases in an Adult Population in the United States in 2023 - Navarrete Pérez , Juan Carlos; Soria Bonilla , Joel Alexander; Suasnavas Arteaga , Karolina; Villacreses , Lissette Carolina; Camino Ortega , Cristina Noemi (Arandu UTIC, 2024)
Background: Given the importance of cardiovascular disease in global morbidity and mortality and its impact on public health, this study was conducted to evaluate the association between marijuana use and cardiovascular disease in a United States population. Methodology: The study employed an observational, cross sectional study design utilizing 2023 Behavioral Risk Factor Surveillance System (BRFSS) database as the data source. Results: The study revealed that marijuana users aged 45-54 years (OR=12.40, CI=6.38-24.07), American Indian individuals (OR=1.74, CI=1.49-2.03), and tobacco users (OR=1.48, CI=1.39-1.57) have a higher risk of cardiovascular disease. After reviewing this study, it is clear that further research is needed to clarify the association between marijuana use and cardiovascular pathology. Conclusion: This study highlights the link between marijuana use and cardiovascular health but calls for further research to clarify its impacts. Findings support targeted public health efforts for at-risk groups.